Biosynthesis of the covalently linked diglyceride in murein lipoprotein of Escherichia coli. - Pabitra Chattopadhyay; Henry C. Wu (1977)
Biosynthesis of the diglyceride moiety of murein lipoprotein in Escherichia coli was studied by pulse-labeling with [2-3H]glycerol and subsequent chase. The evidence strongly suggests that the precursor of the glycerol moiety in lipoprotein is one of the major phospholipid species in E. coli. Studies of biosynthesis of lipoprotein in cerulenin-treated cells indicated that the nonacylated glycerol moiety of phosphatidylglycerol is the donor for the formation of a thioether linkage in the glycerylcysteine residue of the lipoprotein. This is supported by the observation that carbon 1 rather than carbon 3 of sn-glycerol is involved in this thioether linkage. We propose that the biosynthesis of lipoprotein proceeds as follows: apolipoprotein + phosphatidylglycerol or acyl phosphatidylglycerol leads to lipoprotein + phosphatidic acid.